ECOLOGICAL EXISTENTIALISM IN JON FOSSE’S NARRATIVES: MEMORY, RESILIENCE, AND INTERCONNECTED WELL-BEING - Kaur, Sukhpreet; Rani, Manju (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present study investigates issues of uncertainty, connectedness, and the human relationship with the environment and memory by examining the intersection of Deborah Bird Rose’s ecological existentialism and Jon Fosse’s I Am the Wind and Aliss at the Fire. Rose’s paradigm, which highlights the dualities of the Anthropocene—uncertainty and interconnectedness—resonates with Fosse’s paintings, distinguished by their existential profundity and eerie depictions of human emotion. Two characters’ metaphorical voyage across the broad sea in I Am the Wind raises existential questions about relationships, identity, and humanity’s precarious bond with the natural world. In a similar vein, Aliss at the Fire explores memory and loss over generations, with nature serving as both a participant and a witness to human tragedy. Echoing Rose’s idea of "shimmer," which recognises the transition between the past, present, and future, the fjord and fire represent cyclical loss and regeneration. This essay argues that Fosse’s depiction of nature as a dynamic force that is both nourishing and destructive offers significant insights into psychological resilience and well-being by applying ecological existentialism to his stories. The pieces emphasise how natural settings and ancestry influence human life, calling for a reconsideration of isolationist viewpoints in favour of interconnection